If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + -10 = -22 Reorder the terms: -10 + c = -22 Solving -10 + c = -22 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + c = -22 + 10 Combine like terms: -10 + 10 = 0 0 + c = -22 + 10 c = -22 + 10 Combine like terms: -22 + 10 = -12 c = -12 Simplifying c = -12
| 4a-16=a-5 | | 16-n/8=-6 | | -2x-9=11+3x | | 21x^2-18x-5=0 | | 7x+3=24+4x | | 8x^3+x^2-55x+42=0 | | x^5-3x^4+10=0 | | 2x^3-6x+3=0 | | -32-3x=5x-37 | | 2=x^2-8+5 | | 1+2x^2-x^4=0 | | 3x(x-5)=4x | | 3(a+2)=-5-2(a-3) | | w/7+9=-3 | | -3(3d-2)=4-d | | 12+5x=2x-11 | | 2x+x^2=224 | | 25=-n/6+(-19) | | 6(a-7)+10=4(a-7) | | 4(5-m)=3(3-2m) | | -8-(y+7)=-6y | | 22y=63 | | x^2+1+3x+6+x=180 | | 4r=2(r-5)-2 | | (x^2+6)(x^5-3x^3-54x)=0 | | 24.75+6x=31.2+3x | | 4-7m=1-6m | | 1.25a=1.222 | | -3=-7t | | 4(x+6)-4=6(x+3)-6 | | 6y-5=7y | | 4x-6=x+49 |